Development of a statistical crop model to explain the relationship between seed yield and phenotypic diversity within the Brassica napus Genepool - Bennett, Emma J.; Brignell, Christopher J.; Carion, Pierre W.C.; Cook, Samantha M.; Eastmond, Peter J.; Teakle, Graham R.; Hammond, John P.; Love, Clare; King, Graham J.; Roberts, Jeremy A.; Wagstaff, Carol (MDPI, 2017)
Plants are extremely versatile organisms that respond to the environment in which they find themselves, but a large part of their development is under genetic regulation. The links between developmental parameters and yield are poorly understood in oilseed rape; understanding this relationship will help growers to predict their yields more accurately and breeders to focus on traits that may lead to yield improvements. To determine the relationship between seed yield and other agronomic traits, we investigated the natural variation that already exists with regards to resource allocation in 37 lines of the crop species Brassica napus. Over 130 different traits were assessed; they included seed yield parameters, seed composition, leaf mineral analysis, rates of pod and leaf senescence and plant architecture traits. A stepwise regression analysis was used to model statistically the measured traits with seed yield per plant. Above-ground biomass and protein content together accounted for 94.36% of the recorded variation. The primary raceme area, which was highly correlated with yield parameters (0.65), provides an early indicator of potential yield. The pod and leaf photosynthetic and senescence parameters measured had only a limited influence on seed yield and were not correlated with each other, indicating that reproductive development is not necessarily driving the senescence process within field-grown B. napus. Assessing the diversity that exists within the B. napus gene pool has highlighted architectural, seed and mineral composition traits that should be targeted in breeding programmes through the development of linked markers to improve crop yields.